KOMPOSISI HASIL TANGKAPAN DAN LAJU TANGKAP (CPUE) USAHA PENANGKAPAN PURSE SEINE DI PELABUHAN PERIKANAN NUSANTARA (PPN) PEKALONGAN, JAWA TENGAH - Dian Ayunita Nugraheni Nurmala Dewi; Iqbal Ali Husni (JFMR (Journal of Fisheries and Marine Research), 2018)
Pekalongan fishing port is a fishing base for purse seiners of small pelagic fish in Central Java. Range of fishing fleets Gross Tonnage is 69 to 125 GT. Purse seine was dominant fishing gear with total percentage 84% from the total fishing gear at Pekalongan fishing port in 2014. The main target of purse seine is shoaling pelagic fish. The objectives of this research were to analyze the catch composition and Catch Per Unit Effort (CPUE) of purse seiners at Pekalongan Fishing Port. The method of this research used survey method. Data analysis with quantitative descriptive method. Analysis conducted on the catch composition and Catch Per Unit Effort of purse seiners. Data to analyze the catch composition was secondary data of purse seiners catches volume in 2016 from January until December. And to calculate the CPUE used secondary data of fishing trips and total production of purse seiners from 2008 to 2016. Variations of dominant type of captured i.e. Shortfin scad, Indian scad, Bali Lemuru, and Indian mackerel. Every month there was different of species dominance caught by the gear ranged from 7 to 11 species. The percentage of each species was Shortfin scad (Decapterus macrosoma) caught dominantly in January, October, November and December. Indian scad (Decapterus russelli) reached the highest percentage in June, July, August and September. Bali Lemuru (Sardinella lemuru) mostly caught in February, April and May. While Indian mackerel (Rastrelliger kanagurta) caught with highest percentage in March (40%). Location of fishing ground was in Indonesia Fisheries Mangement Area with code 712 and 713. The annual average CPUE of purse seine in Pekalongan Fishing Port was 18,712 kg or 18.7 metric tonnes per trip for each fleet. This result shows that the productivity of purse seiners was quite low compared with the size of fishing fleet Gross Tonnage 69 up to 125 tons.